Ibero-American modernity from the economic key: an Echeverrian contribution to critical history - Véliz Catalán, Néstor (2020)
This article begins by exploring the incorporation of the echevarrian “economic key” to the methodologyof Critical History. Next, it is discussed how the form assumed by the movement of the forcesof capital conditioned the irruption of modernity in Ibero-America. In this sense, the next sectiontries to understand the integration of the region into the system from the accumulation of “capitalistevents”; the work concludes by addressing, from the perspective of Bolívar Echeverría, howcapital became the backbone of Ibero-American modernity, bringing various unfavorable economicconsequences for the majority.